Simulation Analysis and Experiment Study of the Fluid- solid Coupled Heat Transfer of Disc Brake - Zeng Hong; Su Guoying; Guo Chao; Wang Yanzhong (Jixie chuandong)
The fluid-solid coupled heat transfer analysis focus on computational fluid dynamics（ CFD）and solid heat transfer finite elements（ FEA）. The partition solving and boundary coupling are used to study a fluid-solid coupled heat transfer system which is formed by every part of brake. By this method,the outer and being difficult to identify borders of a single part heat transfer can be transformed into inner borders,it can only define the external borders for calculating,which is more practical and easier to calculate. Comparison between simulation and measurement data shows that the simulation data are in good agreement with experimental results. So,taking the coupling method to simulate brakes thermal conduction and heat convection is feasible.